Pesticide and Container Disposal for Homeowners - Olaf Norman Nesheim (EDIS, 2002)
This document is PI-27, one of a series of the Pesticide Information Office, Food Science and Human Nutrition Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Adapted from a Clemson University Home and Garden Information Center information sheet prepared by Robert G. Bellinger, Extension Pesticide Coordinator, Clemson University. Published August 2002.